“EmosiAn”: An android-based application for handling students with mild depression in MAN 1 Yogyakarta - Janneta Filza Auladwasasyah; Ika Rahmanita; Hersa Ajeng Priska; Nasution Nasution; Alwan Nur Fakhry; Nur Aisyah Jamil (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Stressors from school and inappropriate friendships could lead to depression among teenagers, and possibly to attempts at suicide if not treated properly. To meet this need, there is a peer counsellor service, which is an extracurricular activity at school, called the Centre for Youth Information and Counseling / Pusat Informasi dan Konseling Remaja (PIK-R) Exalta. However, only a few students have used this service. This was due to a situational barrier that happened in direct counselling. This study aimed to detect mild depression and evaluate the implementation of the EmosiAn application (app) in handling mild depression among students. This study used secondary data from Program Kreativitas Mahasiswa Pengabdian Masyarakat (PKM-M)/ Student Creativity Program-Community Services conducted from Augustus to October 2020 at MAN 1 Yogyakarta. A total of 126 students voluntarily filled out the Patient Health Questionnaire-9 (PHQ-9), and 47 (37.3%) showed mild depression. Among 27 students and 5 peer counsellors then agreed to participate. The EmosiAn app was designed based on their problems, and had two interfaces for the administrator (peer counsellor) and the user (student). The app contained a diagnosis of depression using PHQ-9, daily journal, chat and reading the relevant articles. Before using the app, both peer counsellors and students attended zoom-online training. There was an increase in peer counsellors' knowledge (p=0.000) and students (p= 0.002) before and after the webinar. All participants could use the EmosiAn app and felt its benefits after two weeks of implementation. There were 40% of students who experienced a reduction of their depression level. Problems encountered during its usage could be resolved by fixing and refining the app. EmosiAn is a user-friendly application used by PIK-R Exalta to detect and care for students with mild depression. Further development is needed for wider used in the future.